2022
DOI: 10.1021/acsomega.2c03148
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Methyl Orange from an Aqueous Solution onto a BPPO-Based Anion Exchange Membrane

Abstract: In this research, the development of a novel brominated poly(2,6-dimethyl-1,4-phenylene oxide) (BPPO)-based homogeneous anion exchange membrane (AEM) via the solution casting method was reported. Fourier transform infrared spectroscopy was used to confirm the successful development of the BPPO-based AEM. The prepared AEM showed excellent thermal stability. It exhibited an ion exchange capacity of 2.66 mg/g, a water uptake ( W R ) of 68%, and a linear swelling ratio of 31%. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 76 publications
0
16
0
Order By: Relevance
“…It suggested that the porous AEM's capacity for adsorption was positively influenced by the EB starting concentration. 19,59 By adjusting the temperature from 273 to 333 K, the impact of temperature on the EB adsorption capacity was investigated. Figure 2d illustrates the impact of temperature on the EB adsorption capacity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It suggested that the porous AEM's capacity for adsorption was positively influenced by the EB starting concentration. 19,59 By adjusting the temperature from 273 to 333 K, the impact of temperature on the EB adsorption capacity was investigated. Figure 2d illustrates the impact of temperature on the EB adsorption capacity.…”
Section: Resultsmentioning
confidence: 99%
“…The porous AEM surface and EB molecules interacted more often. It suggested that the porous AEM’s capacity for adsorption was positively influenced by the EB starting concentration. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adsorptions of MO dye by geopolymer and modified geopolymer with dose of 2 g.L -1 were performed in batch process at various pH (2,4,7,10,12), time (15,30,45,60,75,90, 105, 120 minutes), and initial concentration of MO dye solution (10,20,30,40,50,60,70,80,90, 100 mg•L -1 ) at room temperature and stirring rate of 200 rpm. The concentration of MO dye solution was analyzed using Thermo Scientific Genesys 10S UV-Vis spectrophotometer.…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, in pseudosecond-order kinetics model, adsorption process is assumed to be controlled by chemical adsorption. As for Elovich kinetics model, adsorption process is assumed to be controlled by chemical adsorption on heterogeneous surface (Benjelloun et al, 2021;Khan et al, 2022;Nizam et al, 2021). Kinetics parameters for each kinetics model can be obtained by plotting linear equation ( 2) for pseudo-first-order model (ln(q e − q t ) versus t), plotting linear equation (3) for pseudo-second-order model (t/q t versus t), and plotting linear equation ( 4) for Elovich model (q t versus ln t) as shown in Figure 7.…”
Section: Kinetics Studies Of Mo Dye Adsorption By Modified Fly Ash-ba...mentioning
confidence: 99%